Wspieranie bardzo małych dzieci z ubytkiem słuchu w Stanach Zjednoczonych Ameryki - Myck-Wayne, Janice; Jakoniuk-Diallo, Anna (Studia Edukacyjne, 2016)
The main objective of supporting the development of children with hearing loss is to optimize the process of acquiring and developing their linguistic competence and communication, despite the existing restrictions in this regard. This task is particularly important in relation to children with hearing parents, because their case involves the removal of barriers to communication between a child with a hearing impairment and his dearest and nearest. Opposite this objective comes out a number of methods, so-called auditory-verbal communication. The purpose of this article is to analyze the use of bilingualism of early support development of deaf children as the most popular model used in the United States. In this country, in which deaf people have won the right to be treated as a cultural minority rather than the disabled, a child with hearing loss has a suitable status predisposed to bilingualism, which entails the need to include it in the interactions supporting the development, discussed in the article.